Unsur Intrinsik Novel KKN (Kuliah Kerja Ngebaper) Karya Nurul Vidya Utami - Shintia Wulandari (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study aims to analyze the intrinsic elements in the novel KKN (Kuliah Kerja Ngebaper) by Nurul Vidya Utami. This novel was selected because it contains various aspects of human life during the Community Service Program (KKN), wrapped in a light yet meaningful romantic and comedic theme. The research employs a descriptive qualitative method with a structural approach, focusing on the analysis of intrinsic elements, which include theme, plot, setting, characters and characterization, point of view, language style, and moral message. The results show that the intrinsic elements in this novel are closely interconnected and together form a coherent narrative structure. The main theme presented is the dynamics of friendship, love, and personal conflict during the KKN activities. A chronological plot is used to portray the story in an orderly manner, with settings that enhance the atmosphere of the narrative. The characters are depicted with diverse and realistic traits. The third-person point of view provides an objective narrative distance, while the moral message conveys deep values about love and sacrifice. This study is expected to contribute to literary studies, particularly in understanding the structure and meaning embedded in modern literary works.